MICROBIAL AND MINERAL CONTENT OF SEWAGE SLUDGE FROM RIYADH AND YANBU, SAUDI ARABIA - Hashem, A. R. (Emirates Journal of Food and Agriculture, 2017)
Sewage sludge samples from Riyadh and the industrial city of Yanbu were analyzed formicrobial and heavy metals content. Twenty one species belonging to 13 genera were isolated from the tested samples. Metal concentration of Al, Cd, Co, Cu, Mn, Ni, Pb and Zn in samples from the industrial City of Yanbu were higher than that of Riyadh samples. The study suggests that the use of sewage sludge without treatment as a soil additive may cause rise to environmental pollution.